PENGENALAN KESEHATAN REPRODUKSI DAN PENCEGAHAN INFEKSI MENULAR SEKSUAL DI SMPN 2 DAN SMPN 6 MATARAM - Octora, Metta; Danianto, Ario; Adni, Azizatul; Prihatina, Lale Maulin; Lasiaprillianty, Intan Wahyu; Wicaksono, Teguh Budi (Universitas Mataram, 2024)
Teenager reproductive health is a health problem that concerns the nation's next generation, with high vulnerability to sexually transmitted infections (STIs). About 1 million transmissions of STIs, such as chlamydia, gonorrhea, syphilis and trichomoniasis occur every day worldwide, and the majority are asymptomatic. Every year, it is estimated 374 million cases are predominantly of reproductive age. This program is based on the trend increasing of promiscuous sexual relations among junior high school teenagers which results in early pregnancy and transmission of STIs. This program has purpose to increase the knowledge of junior high school students and teachers regarding sexually transmitted infections and reproductive health as well as preventing free sex. Counseling regarding reproductive health and sexually transmitted infections is carried out at SMPN 2 and SMPN 6 in Mataram. Extension activities include providing outreach materials, interactive question and answer sessions, Instagram competitions on related topics. The mean post-test score of participants was significantly higher than the pre-test (p <0.05). The scores of SMPN 6 students were found to have a significant increase in the mean during the post-test compared to the pre-test (p <0.05). There was a change in the knowledge of SMPN 2 and SMPN 6 Mataram students regarding reproductive health and STIs after the counseling